PEMETAAN PENGGUNAAN TEKNOLOGI KEUANGAN DALAM PENGELOLAAN KEUANGAN PERSONAL PADA KELOMPOK GEN Z DI SUBANG - Estu Widarwati; Erika Safrina Azizah; E. Wityasminingsih (STIESA-PRESS, 2025)
The rapid digitization of financial services is driving the role of financial technology in revolutionizing the payment system through innovations such as e-wallets and online lending. In addition, it is important to explore the diversity of a demographic group to understand their financial independence and behavior. This study investigates the impact of financial technology on personal financial management among university students in Subang, West Java. Furthermore, this study aims to analyze the application of technology that affects budgeting, spending, and overall financial decision-making among university students. The mapping of used financial technology was conducted in September 2024 with 30 randomly selected Gen Z students from various universities in Subang. The stages of implementing activities include distributing structured questionnaires and evaluating feedback using quantitative, descriptive, and exploratory approaches. Using a quantitative approach, data were collected through questionnaires distributed to students. Findings indicate that financial technology has a significant impact on personal financial management practices, leading to improved financial budgeting and monitoring. This mapping highlights the importance of integrating financial technology into financial education, providing valuable insights for policymakers and financial technology service providers to tailor their offerings to meet the needs of young consumers.